2014
DOI: 10.3390/jpm4020200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Technology on the Therapy of Type-1 Diabetes: A Case Study of Children and Adolescents in Germany

Abstract: Being able to manage and adjust insulin doses is a key part of managing type-1 diabetes. Children and adolescents with type-1 diabetes mellitus often have serious difficulties with this dosage adjustment. Therefore, this paper aims to investigate the impact of using novel mobile, web and communication technologies in assisting their therapy and treatment. A trial was conducted in the north-eastern part of Germany to evaluate the impact of the “Mobil Diab”, a mobile diabetes management system, on the clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 31 publications
4
94
0
2
Order By: Relevance
“…275,278,283,285 Of these, improvements were also seen in the control group, 275 and no significant differences between the intervention and control were reported after 6 months. 283 Three studies reported no reduction in HbA 1c levels following DCC interventions 279,281,284 and five studies found no differences when the intervention was compared with a control.…”
Section: Patient Outcomesmentioning
confidence: 88%
See 3 more Smart Citations
“…275,278,283,285 Of these, improvements were also seen in the control group, 275 and no significant differences between the intervention and control were reported after 6 months. 283 Three studies reported no reduction in HbA 1c levels following DCC interventions 279,281,284 and five studies found no differences when the intervention was compared with a control.…”
Section: Patient Outcomesmentioning
confidence: 88%
“…Two studies reported no differences in quality of life between the intervention and control groups. 250,276,283 There were also mixed findings in relation to self-efficacy: two studies found that self-efficacy and self-management increased in the intervention group, 275,277 whereas one found no differences. 276 In the qualitative pilot study, patients reported benefits to the intervention.…”
Section: Patient Outcomesmentioning
confidence: 95%
See 2 more Smart Citations
“…At a mandatory consultation, the diary was discussed and patients and providers reflected on its recordings (n=12; ages 13-19). Berndt et al [33] tested an application to collect data and provide clinical support in a four-week RCT (n=68; ages 8-18). Finally, Goyal et al [34] tested an mHealth application in a 12-month RCT (n=92; ages 12-15).…”
Section: Discussionmentioning
confidence: 99%